The Coincidence Between Increasing Age, Immunosuppression, and the Incidence of Patients With Glioblastoma - Ladomersky, Erik; Scholtens, Denise M.; Kocherginsky, Masha; Hibler, Elizabeth A.; Bartom, Elizabeth T.; Otto-Meyer, Sebastian; Zhai, Lijie; Lauing, Kristen L.; Choi, Jaehyuk; Sosman, Jeffrey A.; Wu, Jennifer D.; Zhang, Bin; et al. (Frontiers in Pharmacology, 2019)
Background: Glioblastoma (GBM) is the most aggressive primary brain tumor in adults, accounting for >50% of malignant glioma diagnoses, and with a median overall survival (OS) of 15-20 months. While immune checkpoint blockade therapy improves the OS of patients diagnosed with some cancers that arise from outside of the central nervous system, a recent phase III clinical trial demonstrating the lack of OS benefit in recurrent GBM patient treated with nivolumab (anti-PD-1 mAb) raises concerns about its applicability against CNS tumors. Less appreciated is elderly nature of GBM, with a median age of diagnosis at 64 years old. Strikingly, our group has previously highlighted the negative impact of advanced age on OS after treating experimental brain tumor models with combination immunotherapy. The connection between aging, immunosuppression, and brain cancer incidence/mortality is unexplored. Methods: Human data was analyzed from the Surveillance, Epidemiology, and End Results (SEER)-, GTex- and 10k Immunomes-databases, for investigating the interactions between brain cancer patient incidence and mortality, with global immunosuppression indices. Results: The proportion of individuals with an age of >65 has been steadily increasing for more than 35 years in the United States (U.S.). Coincident with the rising number of elderly individuals, the brain cancer mortality rate is also increasing. Advanced age maximally increases several dominantly immunosuppressive factors in healthy individuals, coinciding with the median age of GBM diagnosis, including the Treg:CD8+ T cell ratio in peripheral blood, as well as increased expression of immunosuppressive IDO1 and PD-L1 in the brain. Conclusion: Although GBM onset is considered to be a disease caused by specific mutations, these novel data highlight the potential for age-dependent factors to increase immunosuppression, which decrease immunosurveillance, and thereby contribute to GBM cell initiation and/or outgrowth.